Penguatan Ekosistem UMKM Melalui Program Pendampingan Terpadu Untuk Mendorong Pertumbuhan Usaha di Kota Serang - Muhammad Nawawi; Nabila Meidina; Teuku Chairumansyah; Khairuddin Khairuddin; Aliyah Sofiyanah; Dian Fadiya Ulfah; Azhra Afifah (Rahmah : Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in strengthening local economies; however, many still face persistent challenges related to managerial capacity, financial literacy, digital adoption, and business networking. This community engagement program aimed to strengthen the MSME ecosystem in Serang City through an integrated mentoring approach designed to foster sustainable business growth. The program employed a participatory and qualitative approach, encompassing needs assessment, collaborative program design, hands-on training, individualized mentoring, and continuous evaluation. The intervention focused on enhancing managerial competencies, improving financial record-keeping, optimizing digital marketing strategies, and fostering collaborative networks among MSME actors. The results demonstrated significant improvements in participants’ business planning capabilities, financial management practices, digital marketing utilization, and entrepreneurial confidence. Moreover, the mentoring process facilitated the emergence of inter-business collaboration and strengthened the local support ecosystem involving universities, communities, and institutional stakeholders. These findings suggest that integrated and context-based mentoring can effectively address multidimensional MSME challenges while promoting adaptive capacity and long-term resilience.